Konsep Laba Dalam Persepektif Syariah: Etis Terhadap Keberkahan Dan Keadilan Ekonomi Bagi Entitas Bisnis - Wiwik Aryanti; Hasni Syanda; Masyhuri (Journal of Islamic Economic Studies, 2025)
In modern business practices, profit orientation is often only focused on quantitative aspects and profit maximization alone. However, in the perspective of sharia, profit has a broader meaning, namely as a result of business that is not only legally halal but also reflects blessings and justice. This study aims to examine the concept of profit from an Islamic perspective and how this ethical approach can be internalized in the management of sharia business entities. The methodology used is a literature study with a qualitative descriptive approach, examining primary sources such as the Qur’an and hadith as well as academic references related to sharia economics and accounting. The results of the study show that sharia business entities need to be the principles of honesty, justice, social responsibility, and blessings as a basis for obtaining and reporting profits. Thus, profit is not only an indicator of financial performance, but also a reflection of contribution to the welfare of the people and business sustainability in the corridor of Islamic values.